Penerapan Pendekatan Whole Language Dalam Pembelajaran Bahasa Indonesia Komponen Reading Aloud Dengan Media Cerita Bergambar - Antica Krisnina Maharani; Mudzanatun; Duwi Nuvitalia (Universitas Ngudi Waluyo, 2023)
Abstract The background that prompted this research was that the whole language approach had not yet been implemented in learning the Indonesian language component reading aloud, shown by the lack of students' understanding of reading aloud, so that many students when asked to read in front of their friends were still embarrassed so the volume was not loud when reading. The purpose of this study was to determine the application of the whole language approach in learning Indonesian with the reading aloud component in class I SDN 1 Protomulyo and to determine students' understanding of reading aloud. This type of research is using a qualitative descriptive approach with data processing and retrieval according to field facts. Data obtained from the results of interviews, observations, practice tests and documentation. The data obtained were analyzed and presented in a descriptive form. The subjects of this research were class I students at SDN 1 Protomulyo. The results of the study showed that by holding 3 meetings, the first meeting the researchers carried out reading aloud practice tests without applying the whole language approach in learning Indonesian with the reading aloud component. From the first meeting activities, there were still many students who could not read aloud. Whereas at the third meeting the researchers carried out practical tests by applying the whole language approach in learning Indonesian with the reading aloud component, many students had experienced improvements in reading aloud. Abstrak Latar belakang yang mendorong penelitian ini adalah belum diterapkannya pendekatan whole language dalam pembelajaran Bahasa Indonesia komponen reading aloud, ditunjukkan kurangnya pemahaman siswa tentang membaca nyaring, sehingga banyak siswa ketika disuruh membaca di depan temantemannya masih malu sehingga volume suaranya tidak nyaring ketika membaca. Tujuan penelitian ini untuk mengetahui penerapan pendekatan whole language dalam pembelajaran Bahasa Indonesia komponen reading aloud pada kelas I SDN 1 Protomulyo dan untuk mengetahui pemahaman siswa tentang reading aloud. Jenis penelitian ini adalah menggunakan pendekatan deskriptif kualitatif dengan pengolahan dan pengambilan data sesuai dengan fakta lapangan. Data diperoleh dari hasil wawancara, observasi, tes praktik dan dokumentasi. Data diperoleh dianalisis dan disajikan dalam bentuk deskriptif. Subjek penelitian ini adalah siswa kelas I SDN 1 Protomulyo. Hasil penelitian menunjukkan bahwa dengan dilakukannya 3 kali pertemuan, pertemuan pertama peneliti melaksanakan kegiatan tes praktik membaca nyaring tanpa menerapkan pendekatan whole language dalam pembelajaran Bahasa Indonesia komponen reading aloud. Dari kegiatan pertemuan pertama masih banyak siswa belum mampu membaca dengan nyaring. Sedangkan pada pertemuan ketiga peneliti melaksanakan tes praktik dengan penerapkan pendekatan whole language dalam pembelajaran Bahasa Indonesia komponen reading aloud, banyak siswa sudah mengalami peningkatan dalam membaca nyaring.